Structure and Diversity In Ombrophilous Forest in the Zona da Mata of Pernambuco - Rosival Barros de Andrade Lima; Luiz Carlos Marangon; Fernando José Freire; Ana Licia Feliciano; Roseane Karla Soares de Silva (Floresta e Ambiente, 2019)
ABSTRACT The objective of this work was to evaluate the arboreal component of a Dense Ombrophilous Lowland Forest fragment through evaluations of richness, structure and diversity. For the sampling of this component, we implanted 40 sample units of 10 × 25 m. We measured all arboreal individuals who presented circumference at breast height ≥ 15 cm, 1.30 m from the ground level. The tree stratum presented 1324 individuals, 100 species, 64 genera and 38 families. The Fabaceae family had the highest wealth and Anacardiaceae was the most abundant. The Shannon index and Pielou equability were 3.60 nats.ind.–1 and 0.78, respectively, suggesting the existence of relevant ecological dominance in the community. The results of this work emphasize the ecological importance of this remnant for maintaining the local flora and fauna, also emphasizing the importance of preserving Atlantic Ombrophilous Forests, particularly in the Zona da Mata of Pernambuco.